HUBUNGAN PENGGUNAAN MEDIA PINTEREST TERHADAP KREATIVITAS SISWA TATA BUSANA SMKN 1 WONOASRI DALAM MEMBUAT DESAIN BUSANA PESTA - Hesty Pragista Putri Susilo; Inty Nahari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to determine the relationship between the use of the social media platform Pinterest and students’ creativity in designing party dresses at SMKN 1 Wonoasri. The background of this study is based on the importance of creativity in the field of fesyen design and the utilization of social media as a source of inspiration in the design process. This research employed a quantitative approach with a correlational method. The population consisted of 72 students, with a sample of 36 students selected using a sampling technique. Data were collected through a questionnaire that had been tested for validity and reliability. The results of the validity test indicated that all items were valid, while the reliability test showed that the instrument had a very high level of reliability. Data analysis included normality test, linearity test, and hypothesis testing. Since the data did not meet the assumptions of parametric analysis, the hypothesis was tested using Spearman Rho correlation. The results showed that there is a significant relationship between the use of Pinterest and students’ creativity, with a correlation coefficient of 0.641 and a significance value of 0.000 < 0.05. The relationship is positive and categorized as strong. In conclusion, the use of Pinterest has a significant relationship with students’ creativity in designing party dresses. The higher the use of Pinterest, the higher the students’ creativity.